Migraine Homoeopathic Approach (Homoeopathy for All, 2024)
Homoeopathy is curative system of  medical branch. In Homoeopathy  patient is treated as a whole.  Each patient having their own  peculiar individual symptoms. In  Homoeopathy physical as well  as mental symptoms are consider  completely. This article is an  attempt emphasizing Homoeopathic  approach migraine. This article also  help in increasing the knowledge on  therapeutic properties of the highly  recommended remedies and useful  rubrics to select most similimum.  And in Homoeopathy migraine  is easily cured if the medicine  symptoms and patient symptoms  are same. If the remedy is selected  properly than it can give spectacular  results. Homoeopathy remedies are  given by watching susceptibility of  the person.
Keywords: Migraine; Homoe opathy; Homoeopathic medicine; Similimum; physical and mental symptoms